The determinants of halal certification adoption among local coffee entrepreneurs in Perlis - Asmadi, Abdul Hakim; Ismail, Ismalaili; Md Sabri, Sabiroh (International Journal of Accounting, Finance and Business, 2025)
In Malaysia, halal certification is critical in ensuring that products meet Islamic standards, fostering consumer trust and confidence. This certification is particularly vital for food and beverage manufacturers, including small and medium-sized enterprises (SMEs), as it directly influences consumer purchasing decisions. Despite its importance, many local coffee shop entrepreneurs remain uncertified, posing challenges to both their market potential and consumer trust. This study investigates the factors influencing the intention to adopt halal certification among local coffee entrepreneurs in Perlis, a state known for its thriving coffee culture, with nearly 100 locally operated coffee shops. The study focuses on four key variables: attitude of entrepreneurs, halal practices awareness, knowledge of the halal concept, and competitive advantage of halal certification, to understand their impact on intention to adopt halal certification. By exploring these dimensions, this research aims to shed light on the barriers and motivators for halal certification adoption, offering actionable insights for policymakers and business owners to bridge the certification gap and enhance competitiveness within the halal market.